2011
DOI: 10.1111/j.1439-0507.2010.01996.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of 188 clinical and environmental isolates of Aspergillus flavus for the new triazole isavuconazole and seven other antifungal drugs

Abstract: Recently isavuconazole, an experimental triazole agent, was found to be active against Aspergillus species. As Aspergillus flavus is the second-most common Aspergillus species isolated from human infection and the fungus has not been widely tested against the drug, we studied a large collection of clinical (n = 178) and environmental (n = 10) strains of A. flavus against isavuconazole and compared the results with seven other Aspergillus-active antifungal agents (some of them triazoles, others echinocandins or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
(108 reference statements)
5
24
1
Order By: Relevance
“…Unfortunately, patient outcome data are not available for these studies, and the impact of voriconazole resistance could not be assessed. Earlier from India, we reported around 5% of A. flavus isolates had high voriconazole MICs (27). Another recent study from India reported two voriconazole-resistant isolates out of a total of 8 A. flavus isolates tested (28).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Unfortunately, patient outcome data are not available for these studies, and the impact of voriconazole resistance could not be assessed. Earlier from India, we reported around 5% of A. flavus isolates had high voriconazole MICs (27). Another recent study from India reported two voriconazole-resistant isolates out of a total of 8 A. flavus isolates tested (28).…”
Section: Discussionmentioning
confidence: 72%
“…A. flavus ATCC 204304 was used as a quality control strain for antifungal susceptibility testing. Antifungal susceptibility testing was also performed by the CLSI (Clinical and Laboratory Standards Institute) broth microdilution technique based on the M38A2 document (27,30,31). Candida krusei ATCC 6258 and A. flavus ATCC 204304 were used as quality control strains.…”
Section: Fungal Isolates Four Clinicalmentioning
confidence: 99%
“…This may be less surprising, as itraconazole and voriconazole MICs are also higher for this species than for A. fumigatus (EUCAST ECOFFs of 4 mg/liter and 2 mg/liter for these compounds, respectively, compared to 1 mg/liter for both agents and A. fumigatus) (17,18). Additional isavuconazole susceptibility studies which used the CLSI method were also analogous (10,12,13,19,20). The clinical implications of these differences in susceptibility within species remain to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…Isavuconazole action includes in vitro activity against Aspergillus and Candida species, although the susceptibility of few clinical isolates has been studied (7)(8)(9)(10)(11)(12)(13). Epidemiological cutoff (ECOFF) values can assist in identifying isolates with raised MICs and/or a greater risk of the presence of a mechanism of resistance.…”
mentioning
confidence: 99%
“…Similarly, Shivaparkash et al studied the antifungal susceptibility profiles of triazoles against a large collection of clinical (n ϭ 178) and environmental (n ϭ 10) strains of A. flavus originating from India, using the Clinical and Laboratory Standards Institute (CLSI) method (21). Posaconazole had the highest activity (GM MIC, 0.123 mg/liter; MIC range, 0.062 to 0.25 mg/liter), followed by itraconazole (GM MIC, 0.177 mg/liter; MIC range, 0.062 to 0.5 mg/liter), isavuconazole (GM MIC, 0.697 mg/liter; MIC range, 0.125 to 2 mg/liter), and voriconazole (GM MIC, 1.167 mg/liter; MIC range, 0.05 to 4 mg/liter).…”
Section: Discussionmentioning
confidence: 99%